Regulation of NFκB Signalling by Ubiquitination: A Potential Therapeutic Target in Head and Neck Squamous Cell Carcinoma? - Morgan, Ethan L. (Cancers (Basel), 2020)
SIMPLE SUMMARY: Head and neck cancer is the sixth most common cancer worldwide and typically caused by smoking and alcohol consumption, or infection with Human Papillomavirus (HPV). Currently, treatment options include surgery, radiotherapy, and/or chemotherapy. However, whilst the survival rate in HPV+ cancer patients is better than those without HPV, survival rates have not improved greatly in recent years, and recurrence rates are high. Ubiquitination is a critical regulatory mechanism that can promote the activation or termination of signal cascades, such as the NFκB pathway, which plays an important role in the pathogenesis and therapeutic resistance of head and neck cancer. In this review, we discuss how NFκB signalling is regulated by ubiquitination and how the ubiquitin pathway is deregulated in head and neck cancer, highlighting how the this pathway may be targeted to inhibit NFκB signalling. ABSTRACT: Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer worldwide, with over 600,000 cases per year. The primary causes for HNSCC include smoking and alcohol consumption, with an increasing number of cases attributed to infection with Human Papillomavirus (HPV). The treatment options for HNSCC currently include surgery, radiotherapy, and/or platinum-based chemotherapeutics. Cetuximab (targeting EGFR) and Pembrolizumab (targeting PD-1) have been approved for advanced stage, recurrent, and/or metastatic HNSCC. Despite these advances, whilst HPV+ HNSCC has a 3-year overall survival (OS) rate of around 80%, the 3-year OS for HPV− HNSCC is still around 55%. Aberrant signal activation of transcription factor NFκB plays an important role in the pathogenesis and therapeutic resistance of HNSCC. As an important mediator of inflammatory signalling and the immune response to pathogens, the NFκB pathway is tightly regulated to prevent chronic inflammation, a key driver of tumorigenesis. Here, we discuss how NFκB signalling is regulated by the ubiquitin pathway and how this pathway is deregulated in HNSCC. Finally, we discuss the current strategies available to target the ubiquitin pathway and how this may offer a potential therapeutic benefit in HNSCC.